Globalization, health and the global south - Amzat, Jimoh, author.
1 online resource
Keywords: "Globalization is a form of social change, reshaping the socio-spatial milieu in which human strive, and in which health and disease are managed and controlled. And yet the effects of globalization are distributed unevenly, with opportunities open for some but not for all. Including further reading and end of chapter discussion questions, this essential textbook will be important reading for students across the health social sciences"--